LE RAISONNEMENT JURIDIQUE SUR LES ÉLÉMENTS CONSTITUTIFS DE L’INFRACTION EN DROIT PÉNAL CONGOLAIS: DU SILENCE DU CODE PÉNAL CONGOLAIS À LA BATAILLE DOCTRINALE - MANDEFU, Socrate LISANGA; Jean-Paul BINDUBUBI MUNEMEH; Gracias OTEMIKONGO MANDEFU (IJRDO Journal of Law and Cyber Crime, 2019)
Turning to the first point, the notion of offenses in Congolese law, beyond the different doctrinal definitions retained in the absence of a legal definition, we classified the offenses according to the various categories while placing particular emphasis on the unjustified choice of the repressive system. Congolese: the offense monism (any violation of the criminal law equals "offense"). Even though the Democratic Republic of Congo has ratified a number of international conventions with repressive systems: the tripartite division, which requires it to modify its monist system in favor of tripartite unlawful division (crimes, offenses and contraventions). After this light on what is meant by an offense in Congolese criminal law, we have scrutinized what is the legal reasoning on the constituent elements of it in the second point. According to these doctrines studied, there are sometimes four elements constituting the offense, sometimes it is three, or sometimes only two. But let us point out that there is in all the studied doctrines, the maintenance of the material element and the moral element. While the others were sometimes maintained, sometimes rejected, even taken as legal basis or the preliminary or the founding element of the offense. However, our position in this doctrinal controversy seems too demanding because we are more globalizing and broad, even rigorous than all the doctrines studied, especially since we count in turn up to six different elements constituting offense, namely: the legal element, the material element, the moral element, the unjust element, the existence of the author and the victim, of which we have described in which each of them is indispensable to the crystallization of an offense, which was not shared by any of the doctrines in this study. Keywords: legal reasoning, offense, elements of offense, Congolese criminal law, doctrine, legal metonymy, criminal mathematics.